2018
DOI: 10.1037/pac0000297
|View full text |Cite
|
Sign up to set email alerts
|

In defiance of the reception logic: The case for including NGOs as human rights monitors in the EU’s policies of first reception of irregular migrants.

Abstract: The first reception system for irregular migrants taking the Mediterranean route into the European Union (EU) is dictated almost solely by border control and security concerns. There is no recognition of the role of nongovernmental organizations (NGOs) as human rights monitors in first reception, and access is limited, controlled, and dependent on local authorities. Newly arriving migrants are at their most vulnerable during first reception. Traumatization and retraumatization brought by violations of human ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…DeBono (2018) argues that policies taken regarding the Mediterranean crossing of asylum seekers into Europe have heightened perceptions of asylum seekers as a threat to security. In 2015, when the European Union developed a “hotspot” approach to processing migrants with irregular entry pathways, the approach emphasized using a crisis framing and criminal processes (e.g., detention, fingerprinting).…”
Section: Perceptions Of Threatmentioning
confidence: 99%
See 2 more Smart Citations
“…DeBono (2018) argues that policies taken regarding the Mediterranean crossing of asylum seekers into Europe have heightened perceptions of asylum seekers as a threat to security. In 2015, when the European Union developed a “hotspot” approach to processing migrants with irregular entry pathways, the approach emphasized using a crisis framing and criminal processes (e.g., detention, fingerprinting).…”
Section: Perceptions Of Threatmentioning
confidence: 99%
“…DeBono (2018) argues that the processes of crisis framing and criminalization facilitate the dehumanization of migrants (Esses, Veenvliet, Hodson, & Mihic, 2008; Esses, Veenvliet, & Medianu, 2012; Haslam & Loughnan, 2014). Dehumanization is a process whereby individuals or groups are perceived as lacking human attributes, such as complex emotions, morality, or warmth, and are thus deemed to resemble animals, or machines (Haslam, Loughnan, Reynolds, & Wilson, 2007).…”
Section: Perceptions Of Threatmentioning
confidence: 99%
See 1 more Smart Citation
“…UMs require psychological support for fear or trauma suffered, although this differs depending on the culture or country of origin (Granero-Molina et al, 2019;Jiménez-Lasserrotte et al, 2020). Nurses confirmed that there continue to be problems in coordinating police and healthcare providers (Chiesa et al, 2019); continuity of care implies separating emergency care from the legal status of UMs (De Bono, 2018). As with other studies, participants face administrative obstacles, communication issues and social and professional stigma (Drewniak et al, 2017;Puchner et al, 2018).…”
Section: Discussionmentioning
confidence: 91%
“…UMs are often affected by chronic diseases, malnutrition, parasitosis, sexual violence and human trafficking (Jiménez-Lasserrotte et al, 2019), as well as dehydration, burns, injuries, myalgias, infectious diseases and urinary retention (Eonomopoulou et al, 2016). After being rescued, the emergency care team provides liquids, food, thermal blankets (De Bono, 2018) and first aid. They also diagnose and treat minor illnesses, and screen for infectious diseases (López-Domene et al, 2019).…”
Section: Introductionmentioning
confidence: 99%